Instability of returns and liquidity during the Covid-19 pandemic: evidence from the brazilian stock market - Brito, Anderson Dias (Revista de Administração da UFSM, 2024)
Purpose: This study aimed to analyze the impact of liquidity on the volatility of the Brazilian stock market, considering the effects resulting from the COVID-19 pandemic. Design/methodology/approach: The sample for this research consisted of the IBOVESPA and the sectoral indices of B3. The analysis covers the period from January 2, 2019, to July 11, 2021. The estimations were performed using the two-regime Markov switching method. Findings: The results show that liquidity has an asymmetric impact on return volatility, both for the IBOVESPA and the sectoral indices. This relationship is more pronounced during the pandemic period than before the crisis. Therefore, this research sought to contribute to the discussion on how the liquidity of the market would impact the returns in a crisis period. This also dialogues with and contributes to the literature in emergent countries on market liquidity and systematic risk. Research limitations/implications: The results of this study do not allow for generalizations, as the data used considers a short time series from a single emerging country. Originality/value: This study provides practical contributions to investors with additional information regarding market liquidity and systemic risk, as it can demonstrate better investment opportunities. There are also contributions to the literature from a behavioral perspective on liquidity and market volatility in an emerging country. Furthermore, the findings provide arguments about market efficiency as well as confirming the asset pricing theory.